Surface structure of few layer graphene. (September 2018) - Zhou, Liangzhi; Fox, Laura; Włodek, Magdalena; Islas, Luisa; Slastanova, Anna; Robles, Eric; Bikondoa, Oier; Harniman, Robert; Fox, Neil; Cattelan, Mattia; Briscoe, Wuge H.
Abstract: Understanding surface structure of graphene is important for its integration into composite materials. Here, we have used synchrotron X-ray reflectivity (XRR) to study the structure of commercially available graphene samples (prepared via chemical vapor deposition, and marketed as graphene monolayers ) on SiO2 /Si at different temperatures. X-ray photoelectron spectroscopy, photoemission electron microscopy and atomic force microscopy (AFM) were employed to evaluate the composition and morphology of the graphene layer. Our results indicate that the samples we characterized consisted of 3–4 layers of graphene, which should thus be more accurately described as few layer graphene (FLG). Furthermore, a "contaminant" layer, comprising polymethylmethacrylate and graphene multilayers, was found present atop FLG. We also report tentative results on the effect of temperature on the graphene sample thickness. At 25 °C, the FLG thickness from XRR measurements was 13.0 ± 1.0 Å, in agreement with that obtained from AFM (13.9 ± 0.7 Å). Upon heating to 60 °C, the FLG thickness expanded to 13.8 Å, which further increased to 14.3 Å upon cooling to 25 °C. We attribute this temperature dependent thickness to the out-of-plane rippling of graphene as previously reported. These unprecedented results on the FLG surface structure are valuable to its potential bioanalytical applications. Graphical abstract: Image 1